The allocation of risk and uncertainty in green infrastructure investment with implications for climate change policy. (3rd April 2019) - Clark, Gordon L.
ABSTRACT: In an era of rising national indebtedness, the public sector is increasingly reliant upon private financial interests for the provision and maintenance of infrastructure. The focus of this paper is upon the allocation of risk and uncertainty between infrastructure investors and between investors and the public. Drawing upon a functional definition of infrastructure and the principles and practices underpinning infrastructure investment, this logic is applied to green infrastructure and a case study of the 'big battery' in South Australia. It is shown how and why private investors may demand that the public sector bear the costs of infrastructure that fall outside of the 'normal' risks obtaining when private capital is put to work to provide collective value. This has significant implications for investing in climate change infrastructure.